2019
DOI: 10.1164/rccm.201801-0119oc
|View full text |Cite
|
Sign up to set email alerts
|

Severe Obstructive Sleep Apnea Is Associated with Alterations in the Nasal Microbiome and an Increase in Inflammation

Abstract: We demonstrate that the presence of an altered microbiome in severe OSA is associated with inflammatory markers. Further experimental approaches to explore causal links are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 53 publications
5
53
0
Order By: Relevance
“…More speci cally, PSQI score was positively correlated with Veillonella and Streptococcus and negatively correlated with Neisseria. These ndings are in-line with those of a clinical study, which reported greater abundances of Streptococcus and Veillonella in the nasal microbial population of patients suffering from severe obstructive sleep apnea (41). Interestingly, whereas a predominance of Neisseria indicates healthy periodontal conditions, an abundance of Veillonella signi es poor periodontal conditions (53).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…More speci cally, PSQI score was positively correlated with Veillonella and Streptococcus and negatively correlated with Neisseria. These ndings are in-line with those of a clinical study, which reported greater abundances of Streptococcus and Veillonella in the nasal microbial population of patients suffering from severe obstructive sleep apnea (41). Interestingly, whereas a predominance of Neisseria indicates healthy periodontal conditions, an abundance of Veillonella signi es poor periodontal conditions (53).…”
Section: Discussionsupporting
confidence: 90%
“…A recent report revealed that the diversity and abundance of oral bacteria differ signi cantly in healthy controls and chronic insomnia patients at multiple taxonomic levels (40). Moreover, the diversity of oral and nasal microbiota increases in diseases such as severe obstructive sleep apnea and halitosis (41,42). In our study, cladograms and LDA scores, the two major outputs of the LEfSe assessment, showed oral microbiome distribution patterns differed in the HYD and NHYD groups at baseline.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…24 Previously conducted cross-sectional, casecontrol, prospective cohort studies as well as randomized controlled trials provided evidence for a positive association between sleep behaviors and inflammatory mediators such as CRP, IL-6, IL-8, TNF-, and von Willebrand factor antigen. 20,32,35,37,40,41,47 However, these studies were heterogeneous with respect to target population as well as definition of sleep behavior, with the majority focused on OSA. We found that hours of sleep were not related to WBC markers, after controlling for sociodemographics, lifestyle, and health characteristics, including periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…A priori confounders for the hypothesized relationships were identified based on the existing literature 16,20,25,26,28,29,[31][32][33][34][35][36][37][38][39][40][41] and classified as sociodemographic, lifestyle, and healthrelated characteristics. Sociodemographic characteristics included age (in years; 30 to 34, 35 to 39, 40 to 44, 45 to 49, 50 to 54, 55 to 59, 60 to 64, 65 to 96, and ≥70), race (Mexican American, other Hispanic, non-Hispanic white, non-Hispanic black, and other), education (<high school, 9th to 11th grade, high school graduate/GED or equivalent, some college or AA degree, college graduate or higher), marital status (married/living with partner, other) and poverty income ratio (<100%, 100% to <200%, and ≥200%).…”
Section: Covariatesmentioning
confidence: 99%